Recurrent Drop Attacks as Presenting Manifestation of Subacute Sclerosing Panencephalitis: An Atypical Presentation - Verma, Rajesh; More, Aniruddha (Journal of Pediatric Neurology, 2018)
Subacute sclerosing panencephalitis (SSPE) is a potentially fatal progressive complication of measles virus infection of the brain occurring in children and adolescents. It typically presents with a progressive decline in cognitive abilities along with periodic myoclonic jerks. We report a case of SSPE with atypical presentation. Our patient presented with intermittent drop attacks without any obvious myoclonic jerks or cognitive decline making his diagnosis difficult. Atypical manifestations of SSPE occur in 10% of patients, and a high index of suspicion is necessary for early diagnosis and management of this dreaded disease.
Keywords: subacute sclerosing panencephalitis; measles virus; drop attacks; cognitive abilities; myoclonic jerks; periodic burst